Sinonasal quality‐of‐life declines in cystic fibrosis patients with pulmonary exacerbations. Issue 2 (13th December 2019) - Safi, Chetan; DiMango, Emily; Keating, Claire; Zhou, Zian; Gudis, David A.
Abstract : Background: In cystic fibrosis (CF), the relationship between chronic rhinosinusitis (CRS) and pulmonary disease is poorly understood. The purpose of this study was to evaluate the relationship between scores on the 22‐item Sino‐Nasal Outcome Test (SNOT‐22) and CF Questionnaire―revised for adolescents and adults over 14 (CFQ‐R 14+), and pulmonary function tests in 2 cohorts of CF patients: those at their baseline health and those with a pulmonary exacerbation. Methods: Patients >18 years old seen in a Cystic Fibrosis Foundation‒accredited clinic completed the SNOT‐22 and CFQ‐R 14+ instruments. Patients presenting for routine care represented the baseline cohort. Patients diagnosed with a pulmonary exacerbation represented the exacerbation cohort. Average SNOT‐22 and CFQ‐R 14+ scores for both groups were compared using a 2‐sample t test, and correlation coefficient was calculated. Results: One hundred three patients were enrolled over 3 months (30 exacerbations and 73 baseline). Patients' mean age was 32 years (56% female and 44% male). Average SNOT‐22 and CFQ‐R 14+ scores were significantly worse for exacerbation patients ( p = 0.001 and p = 0.0003, respectively). Percent predicted forced expiratory volume in 1 second and forced vital capacity were both higher for baseline patients ( p = 0.002 and p = 0.001, respectively). Average SNOT‐22 score for all patients was worse than the average score for non‐CF, non‐CRS patients. Conclusion: CF patients with pulmonary exacerbations have worse SNOT‐22 and CFQ‐R 14+ scores than CF patients at their baseline health. This finding suggests a temporal relationship between sinonasal and pulmonary quality of life, and that worsening of both is associated with reduced pulmonary function.